AKSIOLOGI DAN ETIKA PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN - Nasution, Donni; Feriyanto, Feriyanto; Mujiatun, Siti (Smart Education, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to managerial decision-making processes. AI is capable of improving efficiency, accuracy, and the speed of data analysis across various managerial functions. However, the utilization of AI also raises axiological and ethical issues, particularly concerning values, responsibility, transparency, fairness, and the social impacts of the decisions generated. This paper aims to examine the axiological and ethical aspects of AI usage in managerial decision-making by highlighting its benefits, risks, and associated moral implications. Through a conceptual approach and literature review, this study discusses the importance of applying ethical principles such as accountability, fairness, and human oversight in the use of AI. The findings indicate that the integration of AI in management must be accompanied by a clear value-based and ethical framework to ensure that the technology provides optimal benefits without neglecting human values and social responsibility